2023
DOI: 10.24875/gmm.m21000480
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and systemic immune-inflammation index in patients with COVID-19-associated pneumonia

Abstract: Introduction: There are hematological parameters that correlate severity and predict mortality mainly in septic and inflammatory states. Objective: To correlate the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammation index (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…Using a cutoff point of 6.6 at admission, they confirmed the diagnostic value of NLR in predicting mortality in patients with COVID-19, with a sensitivity of 100% and an accuracy of 79.2% [ 37 ]. Similar results consistent with these studies were also reported in 2020 and 2021 b y different authors [ [38] , [39] , [40] ]. Considering the studies by Holub et al (2012) and Naess et al (2017), who used NLR to distinguish between viral and bacterial infection, it is plausible that the patients who died in the present study must have had an accompanying bacterial infection that exacerbated their clinical evolution [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using a cutoff point of 6.6 at admission, they confirmed the diagnostic value of NLR in predicting mortality in patients with COVID-19, with a sensitivity of 100% and an accuracy of 79.2% [ 37 ]. Similar results consistent with these studies were also reported in 2020 and 2021 b y different authors [ [38] , [39] , [40] ]. Considering the studies by Holub et al (2012) and Naess et al (2017), who used NLR to distinguish between viral and bacterial infection, it is plausible that the patients who died in the present study must have had an accompanying bacterial infection that exacerbated their clinical evolution [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, analyses with a larger number of patients, in a longitudinal approach, and with subgroup analyses should be performed. Despite the lack of novelty, our results confirm similar observations published by different authors [ 6 , 19 , 21 , 31 , [36] , [37] , [38] , [39] , [40] , [41] ] and suggest that the assessment of these biomarkers at the baseline of hospitalization can predict the severe outcome of patients with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Excess neutrophils in severe cases are likely to cause a compensatory decrease in lymphocytes during the progression to severe COVID-19. NLR, a biomarker of systemic inflammatory response, predicted admission to the ICU in severe patients [41][42][43][44]. In our study, NLR was an independent predictor of mortality in obese patients;1 probably because it reflects the inflammatory severity of COVID-19 added to the chronic inflammation of these patients (previously demonstrated by greater levels of IL-6 and CRP in the blood) [45,46].…”
Section: Mortality and Predictors For Mortalitysupporting
confidence: 49%
“…Though NLR is a widely used inflammatory marker, it is not sufficient alone for the detection of COVID-19 infection. 33 Also, it is difficult to detect an exact cut-off value, as it had been demonstrated that the cut-off varies according to the population and race. 34 So, combining the assessed inflammatory indices together with different sensitivity and specificity levels could add value to COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%